Optimal estimator of hypothesis probability for data mining problems with small samples - Piegat, Andrzej; Landowski, Marek (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a new (to the best of the authors? knowledge) estimator of probability along with a theoretical derivation of its optimality. The estimator is especially suitable for a small number of sample items, which is the feature of many real problems characterized by data insufficiency. The control parameter of the estimator is not assumed in an "a priori", subjective way, but was determined on the basis of an optimization criterion (the least absolute errors).The estimator was compared with the universally used frequency estimator of probability and with Cestnik's m-estimator with respect to accuracy. The comparison was realized both theoretically and experimentally.
Keywords: single-case problem; probability; probability estimation; frequency interpretation of probability; completeness interpretation of probability; uncertainty theory